Preoperative Warming Versus no Preoperative Warming for Maintenance of Normothermia in Women Receiving Intrathecal Morphine for Cesarean Delivery: A Single-blinded, Randomized Controlled Trial. Issue 3 (September 2018) - Munday, J.; Osborne, S.; Yates, P.; Gosden, E.
Abstract : ( Anesth Analg . 2018;126:183–189) In women undergoing cesarean delivery, a cooling of core temperature to below 36°C during surgery and the postoperative phase is associated with detrimental physiological effects and adverse neonatal outcomes. The rates of perioperative hypothermia in this population range from 32% to 80%. Although current guidelines advise 30 minutes of preoperative warming as a prophylactic measure, there have been studies showing that that 15 minutes plus continuation of forced air warming during surgery has efficacy. The authors of the present study compared the effects of a 20-minute preoperative period of forced air warming plus intraoperative intravenous (IV) fluid warming on women receiving intrathecal morphine during elective cesarean delivery to that of women receiving IV fluid warming alone.